The public’s comfort with sharing health data with third-party commercial companies - Trinidad, M. Grace (Humanit Soc Sci Commun, 2020)
Healthcare systems are using big data-driven methods to realize the vision of learning health systems and improve care quality. In so doing, many are partnering with third-party commercial companies to provide novel data processing and analysis capabilities, while also providing personal health information to a for-profit industry that may store and sell data. In this research we describe the public’s comfort with sharing health data with third-party commercial companies for patient and business purposes and how this comfort is associated with demographic factors (sex, age, race/ethnicity, education, employment, income, insurance status, and self-reported health status), perceived healthcare access, and concerns about privacy. We surveyed the US public (n = 1841) to assess comfort with sharing health data with third-party commercial companies for patient or business purposes and examined whether there was a difference between comfort with data sharing for patient or business purposes. Univariate and stepwise regression modeling is used here to estimate the relationship between comfort with third-party commercial companies for patient and business purposes (outcomes) and demographic factors, self-reported health status, perceived healthcare access, and privacy concerns. The public is more comfortable sharing health data with third party commercial companies for patient purposes as compared to business purposes (paired t = 39.84, p < 0.001). Higher education was associated with greater comfort with sharing health data for patient purposes (β = 0.205, p < 0.001) and decreased comfort with sharing health data for business purposes (β = −0.145, p = 0.079). An inverse relationship exists between privacy concerns and comfort with sharing health data for both patient (β = −0.223, p < 0.001) and business purposes (β = −0.246, p < 0.001). Participants ages 45–59 were less comfortable sharing health data with third party commercial companies for patient purposes (β = −0.154, p = 0.0012) than participants aged 18–29. Proactive acknowledgment of privacy concerns and better communication of the steps being taken to protect the privacy of health data can increase patient comfort. Healthcare systems may be able to increase public and patient comfort with sharing health data with third-party commercial companies by emphasizing the patient-centered benefits of these partnerships.